Factors related to self-care behavior for stroke prevention amongst hypertensive patients in Mae Chai District, Phayao Province - Narongdate, Narongdate; Lamluk, Prachuab; Sirinual, Suthichai (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This cross-sectional descriptive research study aimed to investigate several aspects related to self-care behavior and its predictors for stroke prevention among hypertensive patients. Specifically, the objectives were to examine: 1) self-care behavior, 2) factors associated with self-care behavior for stroke prevention, and 3) predictive factors for stroke prevention behavior in a population of hypertensive patients residing in Mae Chai District, Phayao Province. The sample size consisted of 400 participants selected through stratified random sampling. Data were collected using questionnaires, and statistical analyses included frequency, percentage, mean, standard deviation, chi-square test, Pearson’s correlation coefficient analysis, and stepwise multiple regression coefficient analysis. The findings revealed that the participants exhibited a high level of health awareness (mean = 2.85, standard deviation = 0.14) and a moderate level of stroke prevention behaviors (mean = 3.56, standard deviation = 0.43). The factors found to be associated with self-care behavior for stroke prevention among hypertensive patients in Mae Chai District, Phayao Province included occupation, perceived risk of stroke, perceived severity of stroke, perceived benefits of stroke prevention, and perceived barriers to stroke prevention behavior. Furthermore, the combined effects of awareness of stroke risk, perception of stroke severity, recognition of the benefits of stroke prevention, and perceived barriers to practicing stroke prevention were able to predict stroke prevention behavior among hypertensive patients in Mae Chai District, Phayao Province, with an accuracy rate of 82.30%.